Effects of Project-based Learning on Students' Learning Performance and Engagement in Computer Science - xue wang; Jirarat Sitthiworachart (My University, 2024)
Attention has been drawn to the benefits of integrating project-based learning (PjBL) into educational curricula to enhance student engagement. This study investigated how well project-based learning fosters student engagement and achievements in computer science courses. Qualitative and quantitative research methods were used for this experiment. A total of 60 first year undergraduate students included in the study were divided into the two following groups: experimental group (n=30) and control group (n= 30). National Survey of Student Engagement’ (NSSE) based on Coates’ five-dimensional framework theory of student engagement was used to collect the data. The results showed that there was no significant difference in the pretest scores between the experimental group and the control group (p >0.05) before the intervention. However, after the experiment, the post test scores of the experimental group were significantly higher than those of the control group (p <0.01), indicating an improvement in engagement. The mean grades and mean engagement of the experimental group were also higher compared to the control group. The difference in engagement between the experimental group before and after the intervention was statistically significant (Z=-3.522, p <0.05), with the median data after intervention being higher than before. Specifically, students engaged in project-based learning (PjBL) were more actively involved in self-perception and self-worth compared to students in traditional learning settings. These findings suggest that highly contextualized project-based learning has a positive impact on student engagement and achievements.
Keywords: Student Engagement; Project-Based Learning; Qualitative property; Problem and Project Based Learning